Age Estimation from Newer Radiographic Methods in Developing and Adult Dentition: Methods and Historical Review (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
In clinical forensic medicine, age estimation plays a key role to answer the status of majority and criminal liability. The preferred dental radiographic method by a forensic expert is the lateral view of lower jaw and age is estimated based on the development/ calcification of the tooth crown and roots. This, however, is a method without intermediate grading and through this article, we make an attempt to highlight other dental radiographic methods (Demirjians 8-teeth method and Pulp-Tooth Area Ratio), which when used in combination with conventional methods may help the expert to estimate age more accurately.
Keywords: Forensic odontology; Age estimation; Demirjian’s method; Pulp-Tooth area Ratio; India